A randomized placebo controlled trial of metformin alone and metformin plus fixed dose combination of cyproterone acetate and ethinyl estradiol in hirsute women with polycystic ovarian syndrome - Jalota, Shivani; Singh, Jatinder; Saini, Ravi (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Polycystic ovarian syndrome is a common endocrine disorder seen in reproductive age group. Hirsutism, oligomennorhea and infertility being the most common chief complaint. Oral contraceptives have shown their efficacy in hirsute females. Metformin, an insulin sensitizer, have also shown some beneficial effects in improving metabolic abnormalities. Aim of this study is to compare the efficacy of metformin alone and metformin with fixed dose combination of cyproterone acetate and ethinyl estradiol in hirsute women with PCOS. Methods: 60 females of PCOS with chief complaint of hirsutism were enrolled. Patients were randomized to either metformin and Diane -35 (35 microgram ethinyl estradiol plus 2mg cyproterone acetate) or metformin and placebo for 9 months. Ferriman Gallwey score and body mass index was calculated at baseline, 3months, 6months and 9 months. FSH/LH/Prolactin/Testosterone/Fasting glucose and Fasting insulin levels were measured at the baseline and at the end of treatment. Results: Majority of females enrolled in the study were in third decade of life. Metformin and Diane- 35 showed higher reduction in Ferriman Gallwey score but Body mass index was reduced in both the groups. There was no significant difference seen between the groups with respect to biochemical profile. Conclusions: This data show that a combination of metformin and contraceptive pill may be more effective in treating hirsutism than metformin alone. Beneficial effects of therapy were seen in relation to BMI as well. Hence, combination therapy is better therapeutic option for treating hirsutism in PCOS.